Taxonomy of ’Euconnus complex’. Part XVII. Status of subgenera defined by male antennal characters: Androconnus Franz and Cladoconnus Reitter (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2018)
Among yet unrevised subgenera of Euconnus, Androconnus and Cladoconnus were originally defined primarily on the basis of male antennal modifications. Based on examination of respective type species, both taxa are maintained as subgenera of Euconnus and redefined to include also cephalic and thoracic structures in their diagnoses.